Indian critiques of Gandhi - Coward, Harold G. (State University of New York Press, 2003)
Annotation. A volume in the SUNY series in Religious Studies Harold Coward, editor.
Includes index.
Keywords: Gandhi, -- Mahatma, -- 1869-1948 -- Political and social views.; Gandhi, -- Mahatma, -- 1869-1948; Gandhi, Mohandas Karamchand, -- (1869-1948) -- Pensée politique et sociale.; Gandhi, Mohandas Karamchand.; India -- History -- Autonomy and independence movements.; India -- Politics and government -- 1919-1947.; Inde -- Politique et gouvernement -- 1919-1947.; HISTORY.; Autonomy and independence movements; Political and social views; Politics and government; India; Indien; Onafhankelijkheidsbewegingen.; Politieke ideeën.; Kritiek (algemeen); Inde -- Histoire -- Autonomie et mouvements indépendantistes.; 1919-1947; History